Form-Focused Instruction in the Heritage Language Classroom: Toward Research-Informed Heritage Language Pedagogy - Kisselev, Olesya; Dubinina, Irina; Polinsky, Maria (Frontiers in Education, 2020)
In the context of adult second language teaching, heritage language speakers have been recognized as a special group of language learners, whose experience with their home language, as well as their motivations for (re)learning it, differ drastically from those of an average learner of a second language. Current heritage language pedagogical approaches focus primarily on the development of communicative (or functional) abilities of the heritage learners and on critical exploration of bilingual practices and identities. However, structural accuracy remains a persistent issue for heritage speakers, who do not always reach higher levels of proficiency in their heritage language (as measured by standard language proficiency tests). In this paper, we use the example of heritage Russian instruction in American college classrooms to argue for the critical role of form-focused instruction in teaching a heritage language, and in particular in bringing heritage learners to greater proficiency. The argument for the importance of form-focused instruction is based on the results of extensive linguistic research combined with insights from the currently available pedagogically oriented research. We formulate and discuss instructional methods that help educators (1) develop heritage learners’ attention to grammatical form, (2) foster heritage learners’ understanding of grammatical concepts, and (3) increase the learners’ metalinguistic awareness. Given consistent parallels across different heritage languages, the methodologies developed for Russian learners can apply to other heritage language classrooms as well, with adjustments based on the sociolinguistic context of particular heritage languages.